Effect of Dillenia suffruticosa extract on dengue virus type 2 replication - Muliawan, Sylvia Y. (Universa Medicina, 2008)
Drugs of plant origin can have easy acceptability as they are non-toxic and inexpensive. Dillenia suffruticosa (D.suffruticosa), also known as Simpoh air in Malaysia, has antibacterial and antifungal activity, but no reported antiviral activity. This led the investigation of this plant against dengue virus type 2 (DV2) replication. Two type of samples: DV2-infected C6/36 cells and uninfected C6/36 cells were prepared. D.suffruticosa extract was prepared in water. The plant extract, D.suffruticosa, was subjected to C6/36 cells with following concentrations, 0.025, 0.05, 0.1, 0.2, 0.4 mg/ml and incubated for 2 hours before infected by DV2. Immobilized non-linear pH gradient strips, pH 3-10 were used in isoelectric focusing, and 10% homogeneous gels were used in sodium dodecyl sulphate-polyacrylamide gel electrophoresis. The results were stained by silver staining for visualization. It was found that NS1 protein expression on infected C6/36 cells was down regulated in intensity of concentrations 0.025, 0.05 and 0.1 mg/ml. However, when higher concentration of D.suffruticosa extract were used (0.2 and 0.4 mg/ml), the cells exhibited slightly reduced NS1 protein spots, when compared to the above concentrations (0.025, 0.05, 0.1 mg/ml). D.suffruticosa extract has an inhibitory effect on the replication of DV2. Non-structural NS1 could be used as a diagnostic marker and/or as a parameter to evaluate the effect of antiviral agents for dengue type 2 virus infection/replication.